Trade Union Growth: A Marketing Model - Gilson, Clive; Spencer, Ian (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
By fusing trade union theory and marketing strategy, this paper provides an interdisciplinary perspective to the study of trade union structure.